Дослідження методів захисту цифрового контенту: DRM і технологія Denuvo - Лісняк, Д. С. (ХНУРЕ, 2024)
The rapid evolution of the distribution of digital content has led to the need to create reliable mechanisms for protecting intellectual property from unauthorised access and distribution. This article examines two main methods of protecting digital content: Digital Rights Management (DRM) and Denuvo technology. DRM acts like a set of locks and keys, controlling who can access digital content and what they can do with it. Denuvo, on the other hand, serves as a sophisticated defence against unauthorised access and piracy, especially in the gaming industry. This article is dedicated to figuring out how to make sure that digital content remains secure in a world where sharing and copying is easy.
Keywords: технологія Denuvo; захист цифрового контенту